SUSCEPTIBILY OF Aeromonar hydrophylla BACTERIA ISOLATED FROM UNHEALTHY BAUNG FISH (Mystus nemurus) TOWARDS ANTIMICROBIAL AGENTS - Pipik Taufik; Dayat Bastiawan (Universitas Gadjah Mada, 2003)
The susceptibility of Aeromonas hydrophila isolated from ikan baung (Mystus nemurus) to antimicrobial agents was carried out. The objective of study is to know the kind of antimicrobial agents for the control aeromonasis of Mystus nemurus. Tryptic soy agar (TSA) plate consisted 106 cells/plate of A. hydrophila on its surface was kept paper disk consisted antimicrobial agent, than incubated on 30 0C for 24 hours. The results showed that from 10 isolates to be tested, 5 isolates were resistant, 2 isolates were intermediate and 3 isolates were sensitive to tetracycline and chloramphenicol respectively; one isolate was resistant, 6 isolates were intermediate and 2 isolates were sensitive to nalidixic acid. Minimal in hibitory concentration (MIC) of tetracycline and chlorampenicol to the sensitive isolates were 0.5 ppm respectively.